Pengaruh Pelatihan Dan Promosi Terhadap Kinerja Pada Unit Personalia Di Badan Kepegawaian Pengembangan Sumber Daya Manusia (BKPSDM) Kota - Siti Rohmah; Yudiyanto Joko Purnomo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted on Bandung City BKPSDM employees. The aim of this research is to determine the description and influence of Training and Promotion on Performance in the Personnel Unit at the Bandung City Human Resources Development Personnel Agency (BKPSDM). The method used in this research is a quantitative method. The population in this study was 36 respondents who took part in training and job promotions. This research uses the census method and uses a questionnaire for data collection. The results of the validity test and reliability test using the Person Product Moment correlation method and Cronbach's Alpha, it is known that the items created are valid and calculations show that partial training has a significant positive effect on performance, while partial promotion has a significant positive effect on performance. The results of calculating the value of the Influence of Training and Promotion simultaneously by looking for the Determination Coefficient shows how much influence there is between the two variables which can be examined from the R value and is 0.743. The value of the r square (R2) is 0.552, so the Coefficient of Determination (KD) is 0.552 x 100%= 55.2%, this means that the influence of training and promotion on performance is 55.2% while the remaining 44.8% is influenced by other variables.